Essential health risk communication for recovery after lifting evacuation orders following the Fukushima Daiichi nuclear power plant accident - Orita, Makiko; Tanaka, Kazutaka; Amir, Isamu; Matsunaga, Hitomi; Kashiwazaki, Yuya; Xiao, Xu; Akata, Naofumi; Miura, Tomisato; Kashiwakura, Ikuo; Ito, Naomi; Abe, Toshiki; Tamaki, Tomoaki; et al. (Scientific reports, 2025)
The Fukushima Daiichi Nuclear Power Plant, managed by the Tokyo Electric Power Company experienced a catastrophic accident in 2011 that led to widespread public anxiety regarding radiation exposure and the long-term impacts of evacuation. The recovery process has considerably varied across the affected municipalities, highlighting the need for effective and targeted risk communication to support residents in understanding these situations and making informed decisions. This study aims to examine the health risk communication strategies implemented by health and medical welfare experts in response to the lifting of evacuation orders in formerly evacuated areas. We provide an overview of the practical activities carried out by these experts, with a particular focus on the contributions of Fukushima Medical University, Hirosaki University, and Nagasaki University. Over the years, these institutions have played a key role in radiation protection and public health initiatives, guided by scientific and technical perspectives. Our findings underscore the necessity of evolving two-way communication practices that are responsive to specific needs of the recovery phase. Additionally, this study highlights the importance of integrating comprehensive health promotion activities with radiation health risk communication to ensure sustained attention to both physical and mental health. Furthermore, expert communication efforts remain essential in supporting social care professionals who are involved in the ongoing care of residents. Finally, the global sharing of Fukushima’s recovery strategies is essential for providing insights that can inform future disaster preparedness efforts.